Chick chorioallantoic membrane (CAM) assay for the evaluation of the antitumor and antimetastatic activity of platinum-based drugs in association with the impact on the amino acid metabolism. (April 2023) - Mitrevska, Katerina; Merlos Rodrigo, Miguel Angel; Cernei, Natalia; Michalkova, Hana; Splichal, Zbynek; Hynek, David; Zitka, Ondrej; Heger, Zbynek; Kopel, Pavel; Adam, Vojtech; Milosavljevic, Vedran
Abstract: The combination of in ovo and ex ovo chorioallantoic membrane (CAM) assay provides an excellent platform which extends its relevance in studying carcinogenesis to the field of screening of anticancer activity of platinum nanoparticles (PtNPs) and further study of the amino acids' fluctuations in liver and brain. PtNPs are promising candidates for replacing cisplatin (CDDP); however, insufficient data of their antitumor efficiency and activity on the cancer-related amino acid metabolism are available, and the assessment of the in vivo performance has barely scratched the surface. Herein, we used CAM assay as in vivo model for screening of novel therapeutic modalities, and we conducted a comparative study of the effects of CDDP and polyvinylpyrrolidone coated PtNPs on MDA-MB-231 breast cancer xenograft. PtNPs showed a higher efficiency to inhibit the tumor growth and metastasis compared to CDDP. The amino acids profiling in the MDA-MB-231 ​cells revealed that the PtNPs had an overall depleting effect on the amino acids content. Noteworthy, more side effects to amino acid metabolism were deduced from the depletion of the amino acids in tumor, brain, and liver upon CDDP treatment. Different sets of enzymes of the tricarboxylic acid (TCA) cycle were targeted by PtNPs and CDDP, and while mRNA encoding multiple enzymes was downregulated by PtNPs, the treatment with CDDP affected only two TCA enzymes, indicating a different mechanism of action. Taken together, CAM assay represents and invaluable model, demonstrating the PtNPs capability of repressing angiogenesis, decrease amino acid contents and disrupt the TCA cycle. Graphical abstract: Image 1